Machine Learning for Data Mining Improve Your Data Mining Capabilities with Advanced Predictive Modeling. - Salcedo, Jesus (Packt Publishing, Limited, 2019)
Most data mining opportunities involve machine learning and often come with greater financial rewards. This book will help you bring the power of machine learning techniques into your data mining work. By the end of the book, you will be able to create accurate predictive models for data mining.